Electrochemical treatment of malachite green dye wastewater by pulse three-dimensional electrode method - Li, Qinghui (Environmental technology, 2024)
Water pollution is becoming more and more serious nowadays, and water resources are in shortage. As an environmentally friendly wastewater treatment technology without secondary pollution, the three-dimensional electrode method has received more and more attention. However, the conventional direct current (DC) three-dimensional electrode method has the disadvantages of high energy consumption and low current efficiency. Based on this, this work investigated the treatment of malachite green (MG) dye wastewater by pulse three-dimensional electrode method. The influences of pulse duty cycle, pulse period, electrolysis voltage, initial pH, aeration rate and Na2SO4 concentration on MG degradation were investigated. The results showed that under the optimal operating conditions of pulse duty cycle of 0.4, pulse period of 15 s, electrolysis voltage of 15 V, initial pH of 5, aeration rate of 0.5 L/min, Na2SO4 concentration of 0.10 mol/L, the removal rates of MG and COD reached 96.2% and 80.5%, respectively, the current efficiency reached 93.4%, and the energy consumption was 24.2 kWh/kg COD after 150 min. Compared with DC power supply mode, the MG removal rate, COD removal rate and current efficiency were enhanced, and the energy consumption was reduced by 83.9%. Moreover, the generation capacity of ·OH was increased under pulse power supply mode. Finally, a possible degradation pathway of MG in pulse power supply mode was inferred using UV-vis and GC-MS analysis. This study indicates that the pulse three-dimensional electrode method is an efficient and low-energy-consumption wastewater treatment method with stable degradation performance for MG dye wastewater